Effective introduction of information technology into modern society - Lasić-Lazić, Jadranka (Array, 2004)
The authors of this paper presume that today we are becoming more and more aware that the whole issue of science and technology is not just a matter of analysing various objects, but a constant reason for political, ethnic, and ecological controversies. We have transformed into a high-risk society in which information revolution is happening at a daily basis. Assuming that technology is indeed a social product and that it serves the purposes of the ruling system of government power, the authors continue to analyse the consequences of these changes. Knowing why and how something may happen instead of just predicting what may happen has become crucial for comprehending social and cultural transformations. According to that today we can observe various expected and planned changes, but at the same time we are also partaking in the processes in which those changes eventually will have absolutely no bearing on the overall socio-cultural development.